Answer:
![f(300)=906](https://tex.z-dn.net/?f=f%28300%29%3D906)
Step-by-step explanation:
![f(x)=3x+6\\\\f(300)=3(300)+6\\\\f(300)=900+6\\\\\boxed{f(300)=906}](https://tex.z-dn.net/?f=f%28x%29%3D3x%2B6%5C%5C%5C%5Cf%28300%29%3D3%28300%29%2B6%5C%5C%5C%5Cf%28300%29%3D900%2B6%5C%5C%5C%5C%5Cboxed%7Bf%28300%29%3D906%7D)
Hope this helps.
One solution was found : t ≤ -13 (number 4)
Pull out like factors :
-3t - 39 = -3 • (t + 13)
Divide both sides by -3
Remember to flip the inequality sign:
Solve Basic Inequality :
Subtract 13 from both sides to get t≤−13
Answer:
71.4
Step-by-step explanation:
The Test
Answer:
80
Step-by-step explanation:
Part (i)
I'm going to use the notation T(n) instead of ![T_n](https://tex.z-dn.net/?f=T_n)
To find the first term, we plug in n = 1
T(n) = 2 - 3n
T(1) = 2 - 3(1)
T(1) = -1
The first term is -1
Repeat for n = 2 to find the second term
T(n) = 2 - 3n
T(2) = 2 - 3(2)
T(2) = -4
The second term is -4
<h3>Answers: -1, -4</h3>
==============================================
Part (ii)
Plug in T(n) = -61 and solve for n
T(n) = 2 - 3n
-61 = 2 - 3n
-61-2 = -3n
-63 = -3n
-3n = -63
n = -63/(-3)
n = 21
Note that plugging in n = 21 leads to T(21) = -61, similar to how we computed the items back in part (i).
<h3>Answer: 21st term</h3>
===============================================
Part (iii)
We're given that T(n) = 2 - 3n
Let's compute T(2n). We do so by replacing every copy of n with 2n like so
T(n) = 2 - 3n
T(2n) = 2 - 3(2n)
T(2n) = 2 - 6n
Now subtract T(2n) from T(n)
T(n) - T(2n) = (2-3n) - (2-6n)
T(n) - T(2n) = 2-3n - 2+6n
T(n) - T(2n) = 3n
Then set this equal to 24 and solve for n
T(n) - T(2n) = 24
3n = 24
n = 24/3
n = 8
This means 2n = 2*8 = 16. So subtracting T(8) - T(16) will get us 24.
<h3>Answer: 8</h3>